KONSEP KEPEMILIKAN ASSET TETAP DALAM AKUNTANSI SYARIAH (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2018)
Allah SWT is the absolute owner of property as explained in the Qur'an An-Nisa, 132 explains: